IMPLEMENTASI GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PRODUKTIVITAS GURU DI SLBN B SUMEDANG - Komala, Puspita; Suliaswati, Suliaswati; Andri Maulana, Andri Maulana; Hanafiah, Hanafiah; Muchtarom, Muchtarom (Wali Pikir: Journal Of Education, 2024)
The leadership style of school principals in special schools with differentiated teacher conditions will have a major influence on the leadership style of principals in special schools. With the differentiated conditions of the school community, the principal in carrying out school management certainly uses special approaches and strategies so that all the interests of the school community can be accommodated well. The leadership style of a school principal will determine the productivity of teachers in the school institution. This research aims to identify the role of leadership as a driver for increasing teacher engagement and productivity. This research was conducted using qualitative methods. The results of this research show that the principal’s transformational leadership can change the way a person thinks and behaves which underlies them in carrying out their duties to be more effective.